Law Enforcement and Overcoming Violations of Money Politic in General Election: Indonesia's Case - Brian Septiadi Daud; Bayu Ardian Aminullah; Nyoman Serikat Putra Jaya (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: The election is a way to choose leaders in both the legislative and executive fields. An election mechanism is also a form of power distribution and its limitation, so elections are an important activity for national development. Through this election, there are evil sparks that can be lit by those who have an evil character; one of these sparks is money politics. Therefore, the implementation of elections required law enforcement agencies to deal with election violations and election disputes under applicable rules.Purpose/Objective Study: The purpose of this study is to find out how law enforcement in violations of money politics in Indonesia and how to deal with its violations.Design/Methodology/Approach: This article is a doctrinal one and using normative legal research methods with a statutory approach. The statutory course referred to is an approach based on legal reviewers related to the problem being discussed.Findings: In this study, the authors found that law enforcement of money politics in general elections in Indonesia must be based on established conditions. Such conditions are like implementing the regulations and force them to be implemented right away. Efforts that must be made in overcoming this violation in general elections in Indonesia are by making pre-eventive efforts. These efforts address election violations from the preparation step until the election implementation step. The second act is preventive actions, namely prevention efforts or non-penal measures before election crime. The third is a repressive effort that deals with corruption and focuses on the nature of the action, eradication, or suppression after the crime.Paper Type: Research Article